Pembelajaran Seni Musik Di SMAN 1 Koto XI Tarusan - Tasnim Kenedi; Jagar Lumbantoruan (FBS Universitas Negeri Padang, 2019)
This study aims to describe the impementation of the music art learning at Xmia2 class in SMA Negeri 1 Koto XI Tarusan. The type of this study was qualitative descriptive. The study object was Xmia2 students in SMA Negeri 1 Koto XI Tarusan that consisted of 23 students. The Instruments used in this study were observation sheet, interview questions and documentation. The result of study shows that the music art learning in SMA Negeri 1 Koto XI Tarusan does not use curriculum 2013, but they use KTSP. In related to the planning of learning, the basic musical theory is arranged becoming 5 indicators. The fifth indicators are not described in purpose of the learning which is purpose of the learning formula focuses on only cognitive domain. It does not include the affective and psychomotor domains yet. The learning materials are factual and procedural. The learning method that is delivered by the teachers is lecture, discussion and assignment. The used media is pianette, meanwhile the teachers use guitar. In the steps of the printed learning in RPP, it uses scientific approach namely doing observation, asking question, doing exploration, associating, communicating, yet in the implementation which is implemented by the teachers, they only doing observation and asking questions. Furthermore, the teachers evaluate the learning to know the level of learning achievement. The fact is the students’ study result are complete.